下顎角部に発生した類腱線維腫の1例 - 足立, 雅利; 松田, 博之; 宮田, 祐介; 金子, 允子 (日本口腔外科学会雑誌, 2010)
Desmoplastic fibroma rarely occurs in the jaw bone. However, we describe our recent experience with this type of desmoplastic fibroma developing in the left angle of the mandible of an 11-year-old girl. The patient had already recognized a lump in the left angle of the mandible about 1 and a half years previously and visited a pediatric clinic, but no definitive diagnosis was made at that time. Because the lump tended to enlarge thereafter, she visited a dental clinic and was then referred to our clinic for a detailed examination. As for the oral findings at admission, a bone-like hard lump was felt in the left angle of the mandible, associated with mild tenderness. Radiographic examination showed a unilocular transparent image with a slightly obscure borderline in the left angle of the mandible. Surgical resection was performed under general anesthesia. The histopathological findings suggested that the lump was composed of fibroblastic cells and collagen fibers. As of 11 months after operation,no local relapse has been noted.